EFFECT OF FISH PROTEIN HYDROLYSATE ON GROWTH, YIELD AND STORABILITY OF SOME FEMALE CUCUMBER HYBRIDS (Cucumis Sativus L) GROWN IN PLASTIC HOUSE IN BASRA - Hassan , Mohammed Khazal; Al-Maliki , Abdul Hussein Qasim; Hamza, Hamza Abbas (Journal for Technology and Science, 2024)
General Background: Cucumber (Cucumis sativus L.) is a widely cultivated vegetable, valued for its nutritional and economic significance. Specific Background: The application of biostimulants, such as fish protein hydrolysate, has gained attention for enhancing plant growth and yield. However, the impact of varying concentrations of fish protein hydrolysate on different cucumber hybrids remains underexplored. Knowledge Gap: Despite existing research on biostimulants, the specific effects of fish protein hydrolysate on hybrid cucumber performance, particularly in unheated plastic houses, are inadequately documented. Aims: This study aimed to evaluate the effects of different concentrations of fish protein hydrolysate on the growth and yield of three cucumber hybrids ("Super Faris," "Ballistic," and "Darina") during the winter agricultural season of 2023/2024. Results: Conducted in a randomized complete block design with six factorial treatments and three replicates, the results indicated that the "Darina" hybrid significantly outperformed the other hybrids in key growth parameters, including plant height, stem diameter, leaf count, fruit number, fruit weight, individual plant yield, total yield, and total dissolved solids. Additionally, concentrations of fish protein hydrolysate at 2 and 4 ml L-1 demonstrated significant benefits over control treatments for most vegetative and yield indicators, although no effect on vitamin C content was observed. Novelty: This study provides new insights into the synergistic effects of hybrid selection and biostimulant application in cucumber cultivation. Implications: The findings suggest that the strategic application of fish protein hydrolysate can enhance cucumber production, highlighting its potential as a sustainable agricultural practice to improve crop yield and quality.